Epochal Enhancing of the Biological Status of Russia’s Population in the 19th - 20th Centuries with Modern Auxology - Mironov, Boris N. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
In 2010-2024 Russian auxologists have expanded the scope of their research. Recently, they have considered height, weight, and body mass index as indirect or proxy indicators of wellbeing, a shift which allows them to identify epochal trends in the dynamics of the standard of living. The results obtained by auxologists confirmed existing conclusions about the upward secular trend of body size and, accordingly, about the epochal increase in the standard of living in Russia in the 19th - 20th centuries. In fact, auxologists have made a sociohistorical turn in terms of biological anthropology, as well as in the field of studying wellbeing, and this has greatly helped Russian historians who do not study anthropometric history. Abroad, this new direction of research has rapidly developed since the 1970s and has already turned into an important academic discipline with its own communities, journals, and departments at universities. According to the author, the most important reason for the indifference of Russian historians to anthropometry is their unpreparedness to work with a new type of source in an interdisciplinary manner including using mathematical and statistical method as well as big data. However, the experience and knowledge of Russian auxologists are of great value for historians. The latter can not only borrow the necessary data from them, but, more importantly, learn from their works the art of conducting anthropometric studies in terms of methodology, analysis methods, and the interpretation of anthropometric indicators.